Sejam $a \in \mathbb{R}$, $a > 1$ e $f: \mathbb{R}->\mathbb{R}$ definida por $f(x) = \dfrac{a^x - a^{-x}}{2}$ A função inversa de f é dada por:


img
ITA IIIT 30/12/2021 17:08
Pela definição da função, podemos escrever:\begin{matrix} y= {\dfrac{a^x - \dfrac{1}{a^x}}{2}} \\ \\ 2y = a^x - \dfrac{1}{a^x} \\ \\ \underbrace{a^{2x} - a^x.(2y) -1 =0} \\ \\ a^x = {\dfrac{2y \ \pm \ 2\sqrt{y^2 - 1} }{2}} \\ \\ {\fbox{ $a^x = y \ \pm \ \sqrt{y^2 - 1} $}} \end{matrix}Como $a^x >0$ e $a>1$: \begin{matrix} x = \log_a{(y \ + \ \sqrt{y^2 - 1})} \\ \\ \fbox{$f^{-1}(x) = \log_a{(x\ + \ \sqrt{x^2 - 1})} \ , $ para $x \in \mathbb{R}$ } \\ \\ \\ Letra \ (C) \end{matrix}
Modo de Edição
0 / 5000
ManualLaTeX